Transformation in higher education : perceptions of female academics at a distance education institution of higher education - Ragadu, Suzette C.; Minnaar, Suzette, C. (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MComm (Industrial Psychology))--University of Stellenbosch, 2007.